Early Warning Score System (EWSS) Impelmentation Factors by Nurses as Early Detection Efforts Worsening of Covid-19 Patients in the Treatment Room - Sulastri, Sulastri; Ma'ruf, Hafidz; Maulana, Hendra (STIKep PPNI Jawa Barat, 2023)
Aims: One way to overcome the Covid-19 outbreak is by intra-hospital management. Fast and accurate management is needed to prevent complications and death in Covid-19. Early detection efforts to detect worsening of Covid-19 patients greatly help prevent more severe complications and death. This study aims to determine the factors of implementing the patient's EWSS in an effort to detect the worsening of Covid-19 in the treatment room at one of the hospitals in East Jakarta. Methods: The research uses descriptive analytic method with a cross sectional approach. Respondents are nurses who are experienced in treating Covid-19 patients in the treatment room with a total of 121 respondents. Bivariate data analysis used the Somers'd test, multiple ordinal regression multivariate test and partial Wald test. Result: Two factors were found that were significantly related to the implementation of EWSS in Covid-19 patients in the treatment room at the hospital, namely the level of knowledge and nurse compliance. Conclusion: This study recommends efforts to increase nurses' knowledge and compliance regarding the implementation of EWSS for Covid-19 patients through regular training, workshops and good supervision.